3D-printed scaffolds with bioactive elements-induced photothermal effect for bone tumor therapy. (June 2018) - Liu, Yaqin; Li, Tao; Ma, Hongshi; Zhai, Dong; Deng, Cuijun; Wang, Jinwu; Zhuo, Shangjun; Chang, Jiang; Wu, Chengtie
Graphical abstract: Abstract: For treatment of bone tumor and regeneration of bone defects, the biomaterials should possess the ability to kill tumor cells and regenerate bone defect simultaneously. To date, there are a few biomaterials possessing such dual functions, the disadvantages, however, such as long-term toxicity and degradation, restrict their application. Although bioactive elements have been incorporated into biomaterials to improve their osteogenic activity, there is no report about elements-induced functional scaffolds for photothermal tumor therapy. Herein, the elements (Cu, Fe, Mn, Co)-doped bioactive glass-ceramic (BGC) scaffolds with photothermal effect and osteogenic differentiation ability were prepared via 3D-printing method. Moreover, the photothermal anti-tumor effect and osteogenic activity of these scaffolds were systematically investigated. The prepared elements-doped scaffolds possessed excellent photothermal performance, which displayed a trend, 5Cu-BGC > 5Fe-BGC > 5Mn-BGC > 5Co-BGC, in this study. The final temperature of elements-doped scaffolds can be well controlled by altering the doping element categories, contents and laser power density. Additionally, the hyperthermia induced by 5Cu-BGC, 5Fe-BGC and 5Mn-BGC effectively killed tumor cells in vitro and inhibited tumor growth in vivo . More importantly, 5Fe-BGC and 5Mn-BGC scaffolds could promote rabbit bone mesenchymal stem cells (rBMSCs) adhesion, and the ionic products released from elements-doped scaffolds significantly stimulated the osteogenic differentiation of bone-forming cells. These results suggested that 5Fe-BGC and 5Mn-BGC scaffolds possessed promising potential for photothermal treatment of bone tumor and at the same time for stimulating bone regeneration, representing a smart strategy for the treatment of bone tumors by combining dual functional bioactive ions with tissue engineering scaffolds. Statement of Significance: The major innovation of this study is that we fabricated the elements (Cu, Fe, Mn, Co)-doped bioactive scaffolds via 3D printing technique and found that they possess distinct photothermal performance and osteogenic differentiation ability. To the best of our knowledge, there is no report about elements-doped scaffolds for photothermal therapy of bone tumor. This is an important research advance by combining the photothermal effect and osteogenic differentiation activity of bioactive elements in the scaffold system for potential bone tumor therapy and bone reconstruction. We optimized the elements-doped scaffolds and found the photothermal effect of elements-doped scaffolds (5Cu-BGC, 5Fe-BGC, 5Mn-BGC) could effectively kill tumor cells in vivo . The photothermal performance of elements-doped scaffolds follows a trend: 5Cu-BGC > 5Fe-BGC > 5Mn-BGC > 5Co-BGC > BGC. Compared to traditional nano-sized photothermal agents, bioactive elements-induced functional scaffolds have better biosecurity and bioactivity. Furthermore, 5Fe-BGC and 5Mn-BGC scaffolds displayed excellent bone-forming activity by stimulating the osteogenic differentiation of bone-forming cells. The major significance of the study is that the elements-doped bioactive glass-ceramics (5Fe-BGC, 5Mn-BGC) have great potential to be used as bifunctional scaffolds for photothermal tumor therapy and bone regeneration, representing a smart strategy for the treatment of bone tumors by combining dual functional bioactive ions with tissue engineering scaffolds.